Correlation of Growth Inhibition Patterns to Nucleoside Transport Models in Neurospora crassa - Magill, Jane M. (1973)
Growth of inhibition patterns provide evidence for a common nucleoside transport or utilization system, a separate system or systems for adenine transport, and another adaptable mechanism of adenosine transport.